2022
DOI: 10.3390/jcm11123514
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Characteristics of Patients with Infective Endocarditis: A Multicenter Study

Abstract: Infectious diseases like infective endocarditis (IE) may manifest or progress differently between sexes. This study sought to identify the differences in demographic and clinical characteristics among male and female patients with IE. Data were obtained from a newly developed registry comprising all adult patients with first IE admission at the four major tertiary cardiovascular centers in West Virginia, USA during 2014–2018. Patient characteristics were compared between males and females using Chi-square test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…However, one study found no significant difference in age between the sexes [ 40 ]. Bhandari et al found this trend true when they found that females admitted for drug use-associated IE tended to be significantly younger than males [ 32 ]. Despite the age differences in developing IE between sexes, it was found that the overall incidence rates of IE progressively increased with age [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…However, one study found no significant difference in age between the sexes [ 40 ]. Bhandari et al found this trend true when they found that females admitted for drug use-associated IE tended to be significantly younger than males [ 32 ]. Despite the age differences in developing IE between sexes, it was found that the overall incidence rates of IE progressively increased with age [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…On average, males comprised 65.8% of patients who developed IE, while females comprised only 34.2% of patients [ 12 , 14 - 19 , 21 - 23 , 26 , 27 , 29 - 31 ]. However, one study done in 2022 found that the incidence of developing IE between males and females was equal [ 32 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations